It looks like you made a mistake in your calculations. Let's go through it step by step:
Given the quadratic equation: 3x^2 + 4x - 1 = 0
To find the solutions using the quadratic formula:
x = (-b ± √(b^2 - 4ac)) / 2a
In this case, a = 3, b = 4, and c = -1
Plugging in the values:
x = (-4 ± √(4^2 - 4*3*(-1))) / 2*3
x = (-4 ± √(16 + 12)) / 6
x = (-4 ± √28) / 6
x = (-4 ± 2√7) / 6
So, the correct solution is:
x = (-4 ± 2√7) / 6
Make sure to double-check your calculations to avoid errors.
Suppose you are a solving a quadratic equation using the quadratic formula and this is your work so far:%0D%0A%0D%0A 3x2+4x−1=0%0D%0A%0D%0A%0D%0A%0D%0Ax=%0D%0A−4 ±42−43−1%0D%0A23%E2%80%8B%0D%0A%0D%0A%0D%0A%0D%0Ax=%0D%0A−4 ±???%0D%0A6%E2%80%8B👈
1 answer